Dampak Partisipasi Sosial pada Keputusan Migrasi Penduduk di Kawasan Bencana - Halima, Ibrohim Abdul; Hanri, Muhammad (Jurnal Kebijakan Ekonomi, 2021)
Natural disasters have caused massive losses in Indonesia, and one of the standard survival strategies implemented by people in disaster areas is to migrate. This study aims to look at the impact of social capital, as measured using participation rates in community activities, on citizens' migration decisions in disaster-prone areas. Using IFLS 5 and DesInventar data, this study found that individual participation significantly reduced migration intensity. The policy implication of this study is that policymakers should leverage and increase existing social capital in society to mitigate the adverse effects of disasters, rather than encourage migration. Key Words:Disaster, social capital, migration, participation